ROLE OF COMMERCIAL RADIO STATIONS IN DISASTER EMERGENCY BROADCASTING (CASE STUDY OF EARTHQUAKE AND TSUNAMI EMERGENCY BROADCASTING PROGRAM IN CENTRAL SULAWESI): Peranan Radio Komersial Dalam Siaran Darurat Bencana (Studi Kasus Siaran Darurat Bencana Gempa Bumi dan Tsunami di Sulawesi Tengah) - Stepanus Bo'do; Andi Akifah; Stella Yulian Moa (Program Studi Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2022)
Access to information is essential when a natural disaster occurs. Fast and accurate information can help residents in finding shelters and surviving the disaster. A community of radio stations has been proven to be a reliable medium for important information in disaster-prone areas. However, due to a series of earthquake, tsunami and liquefaction events in Palu and Donggala in September 2018, the role of radio stations community was taken over by private commercial broadcasters. Using a case study strategy, this study aims to determine the role of private local radios in emergency broadcasting during the response, post-disaster recovery and reconstruction period. Data was collected through in-depth interviews and document analysis. The results of the study found that during the handling and recovery period, commercial radio stations switched to functioning as community radio by changing the broadcast program (switching) into fully emergency broadcast radio. The emergency radio broadcasting initiative from the First Response Indonesia agency allows several private commercial radio broadcasts that have been damaged and looted to perform emergency broadcasts for six months. This program fulfills citizens' basic right of information and supports post-disaster handling and recovery efforts. As the program ended, private commercial radio stations struggled to continue to contribute to the reconstruction phase of the disaster. Support to stabilize the community radio stations initiative is required in disaster-prone areas such as Central Sulawesi.